Development and validation of the Portuguese version of the WHOQOL-OLD module - Fleck, Marcelo P; Chachamovich, Eduardo; Trentini, Clarissa (Revista de Saúde Pública, 2006)
OBJECTIVE: The increasing proportion of older adults in the general population and the specific characteristics of this age group show the need for the development of specific instruments to measure quality of life in older adults. The study aimed at describing the development and validation of the Portuguese version of the World Health Organization Quality of Life for Older Persons (WHOQOL-OLD) module. METHODS: The WHOQOL-OLD instrument was administered in a sample of 424 older adults in the city of Porto Alegre, Southern Brazil, in 2005. The questionnaire comprises 24 items divided into six facets: sensory abilities; autonomy; past, present and future activities; social participation; death and dying; and intimacy. Besides the WHOQOL-OLD module, the WHOQOL-BREF, BDI and BHS instruments were also applied. The instrument's internal consistency was assessed using Cronbach's alpha coefficient. RESULTS: The instrument showed adequate internal consistency (Cronbach's coefficients ranging from 0.71 to 0.88), discriminant validity (p